Answer:
1)
![\boxed{p(x) = x^3-x^2+x-1}](https://img.qammunity.org/2021/formulas/mathematics/college/tln14ul69dovcjlz3bjs0j145mpu6t86g5.png)
2)
![\boxed{p(x) = x^2+x-2}](https://img.qammunity.org/2021/formulas/mathematics/college/4jkgfdwtd2f96gv3ef7uwokf0y0oawepjg.png)
3)
![\boxed{p(x) =- 2x^2+2x+4}](https://img.qammunity.org/2021/formulas/mathematics/college/55dur5pscgd66f502bprh5zdsn0avv57nf.png)
4)
![\boxed{p(x) = 2x^2+x-4}](https://img.qammunity.org/2021/formulas/mathematics/college/3cnoh8pm61oid3n2yeyjvbzgoaoyjc0kgo.png)
Explanation:
Part (1)
![p(x) = x^3-x^2+x-1](https://img.qammunity.org/2021/formulas/mathematics/college/fad9xb7jrecv3tdo7wuwyyrf87vwhdkn23.png)
As we have to determine it by ourselves, this is the polynomial having a degree of 3. p(x) with a degree of 3 means that the highest degree/exponent of x should be 3.
Part (2)
![p(x) = x^2+x-2](https://img.qammunity.org/2021/formulas/mathematics/college/2k06prc1lzp2xmcrtvm6fndooz5bp5jl6m.png)
This can be the polynomial having the factor x-1 because if we put:
x - 1 = 0 => x = 1 in the above polynomial, it gives us a result of zero which shows us that (x-1) "is" a factor of the polynomial.
Part (3)
![p(x) = -2x^2+2x+4](https://img.qammunity.org/2021/formulas/mathematics/college/u2t8w86zaspcu7ktq8bkqi15ckex1r8lkw.png)
This can be the polynomial for which p(0) = 4 and p(-1) = 0
Let's check:
![p(0) =- 2(0)^2+2(0)+4\\p(0) = 0 + 0+4\\p(0) = 4](https://img.qammunity.org/2021/formulas/mathematics/college/8wipiowr5y1iy5wfr7elazlubwoyri7udd.png)
![p(-1)= -2(-1)^2+2(-1)+4\\p(-1) = -2(1)-2+4\\p(-1) = -2-2+4\\p(-1) = 0](https://img.qammunity.org/2021/formulas/mathematics/college/s4m8x9okdipui9s42phjqldysv0307dq1w.png)
So, this is the required polynomial determined by "myself".
Part (4):
![p(x) = 2x^2+x-4](https://img.qammunity.org/2021/formulas/mathematics/college/vx306bhdhvt86bxly5ttnzpl6s894jyj6h.png)
This is the polynomial having a remainder 6 when divided by (x-2)
Let's check:
Let x - 2 = 0 => x = 2
Putting in the above polynomial
![p(x) = 2(2)^2+(2)-4\\Given \ that \ Remainder = 6\\6 = 2(4) +2-4\\6 = 8+2-4\\6 = 10-4\\6 = 6](https://img.qammunity.org/2021/formulas/mathematics/college/eegdynzvv2aiwti6d9gwtntx0l3wz9qrax.png)
So, Proved that it has a remainder of 6 when divided by (x-2)